Rhetorical Speculations : The Future of Rhetoric, Writing, and Technology - Sundvall, Scott (Book collections on Project MUSE., 2019)
"Allows scholars to explore modes of critical speculation into the transformative effect of emerging technologies, to speculate future shifts in intellectual, pedagogical, and institutional frameworks. The project repositions scholars as proprietors of our technological future rather than as secondary receivers, critics, and adjusters of the technological present"--Provided by publisher